ANALYSIS AND NECESSITY OF THE FINANCIAL CONDITION OF THE ENTERPRISE: FINANCIAL AND ECONOMIC - Babadjanov Abdirashid Musayevich (American Journals Publishing, 2024)
This article describes the analysis of the financial position of economic entities and the fact that scientific research is carried out on the shortcomings that arise in the financial report during the period of the enterprise's activities.In the implementation of the activities of the Enterprise, each economic entity must analyze the financial condition of its enterprise. The need for financial analysis at the enterprise is considered and determined during the analysis, the classification of types of financial analysis, which affects the financial and economic condition of the enterprise, reflects the main users of its financial data, and also methodical methods of financial analysis of the enterprise are considered. Scientifically based conclusions have been developed on the results obtained from the analysis of the financial condition of business entities.
Keywords: Financial status, financial analysis, solvency, methods, financial stability.